PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI MODEL PBL DI KELAS VIII SMP NEGERI 2 WERU - Munawarotun, Tri Rif'atun; Sati, Sati; Andayana, Iwan (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to increase student learning motivation through the application of Problem Based Learning (PBL) model integrated with Teaching at The Right Level (TaRL).learning. The research was conducted in class VIII-H SMP Negeri 2 Weru, Cirebon Regency using the Classroom Action Research (PTK) method for two cycles. Data were obtained through observation of student learning activities based on five indikators of learning motivation, namely perseverance, resilience to challenges, interest, success, and independence in learning. The results showed an increase in student learning motivation from the low category in the pre-cycle (31.9%) to moderate in cycle I (68.2%) and high in cycle II (81.6%). The integration of TaRL in the PBL model is proven to strengthen the active role of students in the learning process through meaningful use of technology, while the differentiation approach accommodates diverse learning needs. Thus, the application of the TaRL -integrated PBL model can effectively increase student learning motivation while supporting 21st century learning that emphasizes active, collaborative, and technology-based engagement